Retención y promoción de docentes en ejercicio del cantón Salcedo - Naranjo Tenorio, Elsa Cristina (2017)
The present work is based on the analysis of retention and promotion of teachers in the canton Salcedo, the objective of this research was to diagnose the current situation of teachers, through a field research; To provide alternatives that improve their work quality, in the educational field of the career of Basic Education at the Technical University of Cotopaxi. Since vocation and teacher training are without doubt the fundamental pillars, nuanced by other elements such as professional recognition, status, continuous training, stability and professional emergence. In order to carry out this investigative process in an appropriate manner, it was necessary to employ methodological techniques and instruments that facilitate the obtaining of information, the use of the scientific observation technique and the survey, designing instruments such as the questionnaire and the fact sheets....